If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5x + 7x + -84 = 42 + -9x Reorder the terms: -84 + 5x + 7x = 42 + -9x Combine like terms: 5x + 7x = 12x -84 + 12x = 42 + -9x Solving -84 + 12x = 42 + -9x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '9x' to each side of the equation. -84 + 12x + 9x = 42 + -9x + 9x Combine like terms: 12x + 9x = 21x -84 + 21x = 42 + -9x + 9x Combine like terms: -9x + 9x = 0 -84 + 21x = 42 + 0 -84 + 21x = 42 Add '84' to each side of the equation. -84 + 84 + 21x = 42 + 84 Combine like terms: -84 + 84 = 0 0 + 21x = 42 + 84 21x = 42 + 84 Combine like terms: 42 + 84 = 126 21x = 126 Divide each side by '21'. x = 6 Simplifying x = 6
| 5a=2-a | | 7z-4=3z+16 | | h=-16t^2+96t+160 | | 6d+20=2d | | A=2a+(n-2)d | | 4*2*x+7=16 | | 10(7p-3)=6(p+8) | | 11x+47=102 | | -k-(-6k)+7+2k-10= | | 2(9n-1)+7(n+6)=-69 | | 1+0.036(175/365)= | | 6x+6=4x+4 | | u+4=12 | | (.66x+x)*2=220 | | 7-12=5 | | -2=x-12 | | 7+3k-12=25 | | 7-12= | | 3x^2-15= | | 7-12/3*4= | | 0.14(y-9)+0.10y=0.04y-0.01(60) | | 60k+80=50k+120 | | 10(6)= | | 7-(-60)= | | 6-5(2m-3)=-29 | | -6(2x-3)+15=19 | | 2.5t+6=10t+24 | | (2x+5)=-2 | | 2x-(3y-(4x-(5y-(6x-7y))))= | | 6g+20=2g+36 | | 4y+19=2y+10 | | 2x+3-5(x+1)=6x+5 |